The use of passive ultrasonic irrigation and photodynamic therapy as an adjuvant in endodontic retreatment associated with endoperiodontal injury (Research, Society and Development, 2022)
Endodontic retreatment continues to be a challenge for Endodontics, as well as supporting techniques that aim to improve and assist in the elimination of microorganisms that have infected root canal systems and led to the development of peripicopathies, such as Passive Ultrasonic Irrigation (PUI) and Photodynamic Antimicrobial Therapy (aPDT) have been frequently used. Thus, the aim of this paper is to report a clinical case of endodontic retreatment of tooth 47 with a diagnosis of endoperiodontal injury associated with periapical lesion. The treatment was carried out in two sessions, using as intracanal medication calcium hydroxide with parachlorophenol with camphor, PUI in both final irrigations and previously the root filling was performed with aPDT. At the end of the treatment it was possible to observe a reduction in the radiolucent areas, suggesting the beginning of bone repair. This case report suggests that PUI and aPDT associated with endodontic retreatment can improve disinfection, favoring the regression of periapical alterations and, consequently, favoring the bone repair process.